Protein folding and metal ions : mechanisms, biology and disease - Gomes, Claudio M., 1970-; Wittung-Stafshede, Pernilla, 1968- (Boca Raton, FL : CRC Press, 2011)
'Interest in the uses and applications of metallo-chemistry in the life sciences continues to expand. This book provides a broad overview of metals and protein folding. It addresses fundamental aspects of the folding, stability, and design of metal binding proteins and peptides along with biological aspects related to the action of metallochaperones. The text features practical information related to methodologies, particular techniques, and bibliographic references. Readers will gain the molecular basis for protein-metal interactions and a good perspective on the applications of protein coordination chemistry in life sciences and biotechnology'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Metalloproteins; Protein folding; Metalloproteins; Metallochaperones; Protein Conformation; Protein Folding; Protein Stability